Facial trauma due to suicide attempt and its implications in a patient with psychological disorder: Brief Report (Research, Society and Development, 2020)
Background: Suicide accounts for a significant share of the world's deaths and is the target of a public health problem. Suicide is unique among the causes of death due to illness, due to the fact that it is a situation in which the individual reaches the extreme of his behavior. The causes are complex and multifaceted and are part of the underlying strategies, stressful life events and personality factors, such as coping strategies adopted in their daily lives. Methods: The objective of this work was to report a clinical case of multiple facial fractures due to a suicide attempt, reporting the multidisciplinary conduct in surgical, psychological and emotional treatment in psychosocial rehabilitation of the patient. Conclusion: Multidisciplinary interaction for the treatment of the patient, with special attention to the nursing team is in contact with the patient, allowing the registration and updated monitoring of their reactions.